2021
DOI: 10.22541/au.161311775.53258136/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Admixture in Africanized honey bees (Apis mellifera) from Panamá to San Diego, California (U.S.A.)

Abstract: The Africanized honey bee (AHB) is a New World amalgamation of several subspecies of the western honey bee (Apis mellifera), a diverse taxon grouped into four major biogeographic lineages: A (African), M (western European), C (eastern European), and O (Middle Eastern). In 1956, accidental release of experimentally bred “Africanized” hybrids from a research apiary in Sao Paulo, Brazil initiated a hybrid species expansion that now extends from northern Argentina to northern California (U.S.A.). Here, we assess n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The nuclear analysis revealed that Mexican honey bee colonies had principally African ancestry and a minor proportion of European racial ancestry, with admixture patterns varying across the country, according to management, beekeeping regions, and latitude. that found a latitudinal effect on African ancestry (Agra et al, 2018;Porrini et al, 2022;Sheppard et al, 1991;Whitfield et al, 2006;Zárate et al, 2022), suggesting that A lineage may be disadvantaged at higher latitudes and altitudes due to lower temperatures and longer winters (Calfee et al, 2020;Harrison et al, 2006). In managed colonies of the Northern beekeeping region, there was a higher decline in the proportion of African nuclear ancestry compared to feral colonies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The nuclear analysis revealed that Mexican honey bee colonies had principally African ancestry and a minor proportion of European racial ancestry, with admixture patterns varying across the country, according to management, beekeeping regions, and latitude. that found a latitudinal effect on African ancestry (Agra et al, 2018;Porrini et al, 2022;Sheppard et al, 1991;Whitfield et al, 2006;Zárate et al, 2022), suggesting that A lineage may be disadvantaged at higher latitudes and altitudes due to lower temperatures and longer winters (Calfee et al, 2020;Harrison et al, 2006). In managed colonies of the Northern beekeeping region, there was a higher decline in the proportion of African nuclear ancestry compared to feral colonies.…”
Section: Discussionmentioning
confidence: 96%
“…These SNPs distinguish between the three lineages most abundant in the Americas: C, M, and A (Chapman et al, 2015). Lineages O and Y have not been detected in the Americas, except for a few reports of O (Magnus & Szalanski, 2010;Zárate et al, 2022). The amplicons containing the SNPs were amplified in four PCR multiplex sets following the authors' recommendations and then sequenced using the MiniSeq platform (Illumina, San Diego, CA, USA) (Chapman et al, 2015).…”
Section: Analysis Of Racial Admixture At Snpsmentioning
confidence: 99%
“…Perhaps most interestingly, in the second common garden experiment (which did test managed and unmanaged colonies), we found that drones from different origins within California did have different patterns of survival, with unmanaged-origin drones being more likely to survive the heat challenge than commercial-origin drones. This is exciting because the experiment was conducted in Southern California, where feral colonies tend to have a greater proportion of African ancestry than the drones from commercial colonies, which originate from Northern California (outside the Africanized zone) [24]. We speculate that colonies surviving without management in Southern California are under continuous natural selection for heat tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a major heat-wave from September 5-7, 2020, in Riverside County caused daytime highs to reach 47 °C [22], and inland counties such as Riverside and San Bernardino are expected to experience higher temperatures during future heat-waves compared to coastal counties, such as Los Angeles [23]. Interestingly, unmanaged (feral) honey bees in Southern California have been genetically characterized and found to contain approximately 25% African ancestry [24]. Since African honey bees survive in hot climates, and unmanaged honey bees in Southern California have been historically exposed to intense heat, we expect bees from this population to possess adaptations to heat and drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation